Ferrugem do eucalipto: análise temporal e quantificação de danos - Rossi, Ana Paula (2013)
The eucalyptus rust, caused by Puccinia psidii, is one of the most important diseases of this crop, making it necessary to know about the progress of the disease over time and the damage it caused. Given the importance of this issue and that the pathogen P. psidii is presenting the eucalypts, the present study aimed to perform a temporal analysis of rust in the field and quantify damage. This study was conducted in the field in the experimental area of Suzano Pulp and Paper Company, located in the municipality of Mucuri - BA. Planted 200 seedlings of clone 2156, hybrid of Eucalyptus grandis x Eucalyptus dunnii, and 200 seedlings of clone 2392, hybrid of Eucalyptus grandis x Eucalyptus urophylla in 3x3 m spacing. The experimental design was a randomized block design with 10 replications in plots of 10 plants for each treatment, and the treatments with and without chemical control. The experiment was divided into two phases, Phase 1: started in April 2005 with the planting of seedlings and adaptation of the seedling, we assessed the incidence of eucalyptus rust, height and biomass of the plant, and the disease incidence and plant height were evaluated in all blocks of the experiment and the biomass in the blocks (1, 2, 3 and 4). For the assessment of biomass was necessary to cut the plants in these four blocks, which occurred when the plants reached six months of age; Phase 2: This phase lasted until 2009, during the four years of the experiment evaluated the height and the diameter of the plants in the remaining six blocks (5, 6, 7 , 8, 9 and 10). With incidence data was performed temporal analysis of rust by evaluating the area under the disease progress curve (AUDPC). Quantification of the damage caused by rust was performed using the time variable (m), biomass (kg) and timber volume (m³) by statistical analysis. When it was not performed chemical control, it was found that the clone 2156 was more resistant toward clone 2392, which can be considered more susceptible, as it showed greater AUDPC. The application of the fungicide triadimenol (Bayfidan) was effective for clone 2392, leading to decreased incidence of rust and providing greater height, biomass and wood volume of plants. This clone was more susceptible to rust, however more productive relative to clone 2156.